THE DUTY OF PROBITY AND POLITICAL PARTIES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The objective of this work will be the study of Art. 23-C of Law nº 8.429/1992, included by Law nº 14.230/2021. By using the analytical-deductive method, from the analysis of the law, doctrine and judicialization of the issue in the Supreme Court, will be discussed the said infraconstitutional rule that left the acts against the public resources of political parties, or their foundations, outside the scope of the civil sanctions applicable by the practice of acts of administrative impropriety. The result will depend on a constitutionally adequate interpretation of the new device, such as the one made in the preliminary decision issued in ADI 7236-DF, by Minister Alexandre de Moraes, of the STF, and that is able to preserve isonomy in the sanctioning treatment, the integrity of public and social assets, democracy and the republican regime. In the final considerations, we highlight the loss of opportunity and the distance between the Law desired by the Constitution and the Law legislated.